2007
DOI: 10.1177/1077558707305424
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Health Disparities in Depressive Disorders Outcomes between Non-Hispanic Whites and Ethnic Minorities

Abstract: There are significant disparities in treatment process and symptomatic and functional outcomes in depressive disorders for racial and ethnic minority patients. Using a life-course perspective, the authors conducted a systematic review of the literature to identify modifiable mechanisms and effective interventions for prevention and treatment at specific points -- system, community, provider, and individual patient -- in health care settings. Multicomponent chronic disease management interventions have produced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 61 publications
(48 citation statements)
references
References 112 publications
0
47
1
Order By: Relevance
“…Case management–based interventions that have successfully narrowed disparities in other patient populations are multicomponent interventions that have simultaneously targeted health care system, provider, and patient factors through a chronic disease management approach (27). Thus ACT’s equity effects could be strengthened if features of the chronic care model (28) that are not considered core elements of ACT were added to it.…”
Section: Discussionmentioning
confidence: 99%
“…Case management–based interventions that have successfully narrowed disparities in other patient populations are multicomponent interventions that have simultaneously targeted health care system, provider, and patient factors through a chronic disease management approach (27). Thus ACT’s equity effects could be strengthened if features of the chronic care model (28) that are not considered core elements of ACT were added to it.…”
Section: Discussionmentioning
confidence: 99%
“…We looked across these reviews and Finding Answers' previous research, [11][12][13][14][15][16][17] and identified several cross-cutting themes. Our findings showed that promising interventions frequently were multi-factorial, targeting multiple leverage points along a patient's pathway of care.…”
Section: Cross-cutting Themesmentioning
confidence: 99%
“…Van Voorhees et al found that multicomponent interventions, using either chronic disease management or collaborative care models that affect the larger health care system, health care organization, provider, and person-level factors, improved the health outcomes of ethnic minorities with depression (Van Voorhees et al 2007). The interventions addressed the continuum of factors in the process from individual patient assessment for depression to navigation through the health care system.…”
Section: Depressionmentioning
confidence: 99%
“…For example, increasing breast cancer screening is only useful if patients have timely diagnostic testing after an abnormal mammogram and appropriate treatment for breast cancer (Masi, Blackman, and Peek 2007). Effective depression interventions addressed evaluation, treatment, completion of treatment, access to providers, and payment (Van Voorhees et al 2007). Some of the most powerful diabetes interventions targeted patient, provider, organization, and community factors simultaneously (Peek, Cargill, and Huang 2007).…”
Section: Multifactorial Interventions That Address Multiple Levers Ofmentioning
confidence: 99%